Edukasi Pengelolaan Sampah Rumah Tangga Melalui Pembuatan Kompos dan Produk Daur Ulang di RT 36 - Fitriani, Yustina; Saputra, Ardhi Iwantara; Khairunnisa, Afifah; Julius, Shello Juliano; Hendika, Gideon Marlyam; Syawal, Nabila Kharida; Meidiana, Alyssa; Sinuhaji, Nia Lorenza Br; Pelealu, Rizky Maulina Malarani; Imanuel, David Kalta; Amrullah, Akbar Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Household waste management has become a serious issue in coastal areas, particularly in stilt-house settlements that lack a structured waste management system. RT 36 Gang Rakyat, located in Klandasan Ilir Subdistrict, Balikpapan Kota District, was chosen as the activity site because the community still tends to burn or dispose of waste indiscriminately and has a low level of awareness regarding waste separation. This community service activity aimed to increase residents’ awareness and skills in waste management. The implementation methods included field surveys, community clean-up and awareness campaigns, demonstrations of compost-making from organic waste, creative recycling training for inorganic waste, and evaluation of the results. The outcomes showed that residents became interested in sorting and processing waste. They successfully produced compost used for medicinal and vegetable plants around their homes and created simple products from inorganic waste, such as tissue holders. This community service activity transformed residents’ perceptions of waste from useless material into a valuable resource. The model has the potential to serve as a sustainable waste management approach that can be replicated in other coastal communities.